PEMBERIAN PUPUK KANDANG TERHADAP PERTUMBUHAN, PRODUKSI BIOMASA PADA BEBERAPA VARIETAS JAGUNG HIBRIDA (Zea Mays) - I wayan Ari Widiantara (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2018)
This research was aimed to determine the effect of beef fertilizer on growth and biomass production in some corn hybrid varieties (Zea mays). This research used completely randomized design factorial 6 x 4 with four replications. The first factor is the corn hybrid varieties were V1 (Bisi-2), V2 (Bisi-16), V3 (Bisi-222), V4 (Nk-212), V5 (Pertiwi-2), V6 (Pacific-224), and the second factor was the level of beef fertilizer were P0 (0 ton/ha), P1 (20 ton/ha), P2 (30 tons/ha), P3 (40 tons/ha). The parameters measured were growth of plant height, the fresh water production and leaf blade percentage of corn hybrid varieties. The results showed that the variety and level of treatment of fertilizer was highly significant effected (P0,01) to the plant high, the fresh water production and leaf blade percentage corn hybrid varieties. Interaction factor were significant effected (P0.05) to the fresh water production, whereas in the growth of plant high and leaf blade percentage did not effected (P0.05). Each treatment was getting the best results in plant height at V2P3 (224 cm), fresh water production at V4P3 (5234 g/plot) and leaf blade percentage at V4P2 (35.35%).